The Impact of Daylight Exposure on Injured Athletes: Implications for Rehabilitation - Marc Niering; Johanna Seifert (International Universities Strength and Conditioning Association, 2024)
During injury rehabilitation and return to competition, various factors impact outcomes, such as psychological parameters, sleep quality, and vitamin D levels. Studies have demonstrated that both natural and artificial daytime lighting can enhance these variables, as well as human health and performance. However, research into therapeutic methods is predominantly restricted to physical or psychological interventions that are costly and time-consuming, rather than integrated solutions. Research on the impact of daylight on injury rehabilitation among athletes is limited. Objective evaluation is necessary to establish effective recovery protocols, providing the rationale for this review. Therefore, this study analyzes existing research and theoretical explanations regarding the effects of daylight on athletes in the rehabilitation process. The results suggest that the underlying mechanism can be organized into sun-induced vitamin D synthesis, cognitive-behavioral processes, the circadian mechanism, and the visual processing of light stimuli. For practical implementation, we propose a cost-effective and time-saving artificial daylight intervention that can serve as an accompanying therapy for injuries. This intervention could be integrated into therapy facilities and sports clubs, for both competitive and recreational sports.